2021
DOI: 10.1002/open.202100088
|View full text |Cite
|
Sign up to set email alerts
|

Fast screening of Depolymerized Lignin Samples Through 2D‐Liquid Chromatography Mapping

Abstract: Lignin valorization and particularly its depolymerization into bio‐aromatics, has emerged as an important research topic within green chemistry. However, screening of catalysts and reaction conditions within this field is strongly constrained by the lack of analytical techniques that allow for fast and detailed mapping of the product pools. This analytical gap results from the inherent product pool complexity and the focus of the state‐of‐the‐art on monomers and dimers, overlooking the larger oligomers. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…43,44 Previous research has also related higher degrees of depolymerization to increased average 1 t R in the GPC-HPLC-UV/ VIS analysis. 37,38 Indeed, PC2 values decrease as a function of reaction time for all experiments as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…43,44 Previous research has also related higher degrees of depolymerization to increased average 1 t R in the GPC-HPLC-UV/ VIS analysis. 37,38 Indeed, PC2 values decrease as a function of reaction time for all experiments as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 78%
“…Previous research has concluded that group 1 mainly contains monomers with propyl and propenyl chains as para -substitutions, group 2 contains monomers with propyl or propenyl chains with oxygen functionalities and group 3 mainly contains dimeric products. 37,38 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to tackle this challenge, De Saegher et al introduced a 2D-liquid chromatography mapping technique (GPC-HPLC-UV/VIS) to characterize and gain insight into the high molecular-weight fragments. 191 We believe that the in-depth characterization of oligolignins will substantially contribute to the valorization of lignin in the future.…”
Section: Green Methods To Adjust the Types Of Oh Groups In Lignin And...mentioning
confidence: 98%
“…Thus, to tackle this challenge, De Saegher et al introduced a 2D-liquid chromatography mapping technique (GPC-HPLC-UV/VIS) to characterize and gain insight into the high molecular-weight fragments. 191 We believe that the indepth characterization of oligolignins will substantially contribute to the valorization of lignin in the future. The different depolymerization techniques are categorized into biocatalytic and chemical techniques, and the latter can be further subdivided into thermal-, acid-and base-catalyzed and oxidative and reductive depolymerization (an overview can be found in Fig.…”
Section: Green Lignin Depolymerization Strategiesmentioning
confidence: 97%